High‐throughput sequencing of peripheral blood for minimal residual disease monitoring in childhood precursor B‐cell acute lymphoblastic leukemia: A prospective feasibility study. Issue 3 (31st December 2021) - Bartram, Jack; Wright, Gary; Adams, Stuart; Archer, Paul; Brooks, Tony; Edwards, Darren; Hancock, Jerry; Knecht, Henrik; Inglott, Sarah; Mountjoy, Edward; Roynane, Marie; Wakeman, Stephanie; et al.
Abstract: Background: Minimal residual disease (MRD) measured on end‐of‐induction bone marrow (BM) is the most important biomarker for guiding therapy in pediatric acute lymphoblastic leukemia (ALL). Due to limited sensitivity of current approaches, peripheral blood (PB) is not a reliable source for identifying patients needing treatment changes. We sought to determine if high‐throughput sequencing (HTS) (next‐generation sequencing) of rearranged immunoglobulin and T‐cell receptor genes can overcome this and be used to measure MRD in PB. Procedure: We employed a quantitative HTS approach to accurately measure MRD from one million cell equivalents of DNA from 17 PB samples collected at day 29 after induction therapy in patients with precursor B‐cell ALL. We compared these results to the gold‐standard real‐time PCR result obtained from their paired BM samples, median follow‐up 49 months. Results: With the increased sensitivity, detecting up to one abnormal cell in a million normal cells, we were able to detect MRD in the PB by HTS in all those patients requiring treatment intensification (MRD ≥ 0.005% in BM). Conclusion: This is proof of principle that using the increased sensitivity of HTS, PB can be used to measure MRD and stratify children with ALL. The method is cost effective, rapid, accurate, and reproducible, with inherent advantages in children. Importantly, increasing the frequency testing by PB as opposed to intermittent BM sampling may allow extension of the dynamic range of MRD, giving a more complete picture of the kinetics of disease remission while improving relapse prediction and speed of detection.